Leadership Strategy of the Head of the Institution in Improving the Quality - Mukarromah, Wardatul; Yaqin, Muhammad Ainul (Journal of Educational Management Research, 2025)
This study aims to understand how the leadership strategy of the institution’s head can improve the quality of the Institute of Social Sciences and Development (LIPS). The focus is on how leaders manage members, build a vision that is open to all, and create an effective, flexible, and sustainable work system. This study employs a qualitative approach, utilizing a case study method, to examine leadership practices in social and religious organizations in greater depth. Data were collected through direct interviews with the institution’s head and members, observations of organizational activities, and official documents owned by the institution. The study's results indicate that the most suitable leadership strategy for LIPS is a participatory and transformative leadership style. This means that leaders encourage cooperation, are open and transparent in communication, provide ongoing coaching, and involve all parties in the decision-making process. This approach has been proven to enhance program quality, foster a stronger work culture within the organization, and encourage active participation from members in achieving common goals. These findings suggest that leaders of social organizations should adopt leadership styles tailored to the field’s specific conditions and grounded in shared values, thereby ensuring the organization’s quality continues to improve comprehensively and sustainably.